Local Ecological Knowledge as a Conservation Tool for Identifying Threats to the Pacific Goliath Grouper (Epinephelus quinquefasciatus) in Panama - Chong‐Montenegro, Carolina; Castellanos‐Galindo, Gustavo A.; Robertson, D. Ross (Aquatic conservation, 2024)
ABSTRACT The Pacific goliath grouper, Epinephelus quinquefasciatus, is the largest reef fish of the tropical Eastern Pacific. The IUCN categorizes it as Data Deficient because of the lack of population data and the risk posed by fishing. Using fishers' local ecological knowledge, we assessed Pacific goliath grouper historical catch trends along Panama's Pacific coast. Handline and speargun catches showed significant declines in the average weight of Pacific goliath grouper landed from 1958 to 2018. Market demand and environmental degradation were identified as primary drivers of the Pacific goliath grouper perceived decline. Local ecological knowledge demonstrated that valuable fisheries information can be derived and used to inform species' population trends.